SOCIAL INTERACTION OF ELDERLY AND ADOLESCENTS IN NURSING HOMES - Raswandaru, Marsela Riska; Eva Rayanti, Rosiana (Jurnal Ilmu Keperawatan Komunitas, 2023)
The White Cross Christian Social Foundation of Salatiga City, Central Java has nursing home and orphanage services. The existence of elderly people and teenagers in the same place of residence still creates a distance in their interaction relationship. Elderly people who are lonely because they are far from their families and teenagers who have lost their parental figures. This research aims to explore the social interactions of elderly and teenagers at the White Cross Social Foundation, Salatiga City. This research was conducted using qualitative methods. The criteria for participants are the elderly and teenagers. The number of participants until data saturation occurred was three elderly and three teenagers. Data collection techniques using semi-structured interviews. Data analysis was carried out using content analysis. Researchers got two themes. First, the perception between the elderly and teenagers regarding generational differences. Second, home activities for the elderly and teenagers. The conclusion from the research results is that the elderly and teenagers come from different generations, so the characters and viewpoints of these two generations are different. The themes obtained need to get the attention of all parties so that social interaction between the two generations becomes more intense because it is part of holistic care that is beneficial for the elderly and teenagers.